The Role of Law in Taxation Policy as an Economic Control Tool: A Case Study of Tax Amnesty in Indonesia - Vanco, Moses; Situmorang, Risma; Salee, Atchara (International Journal of Contemporary Sciences (IJCS), 2024)
This study examines the role of law in Indonesia's tax amnesty policy as a means of economic control. Using normative legal research, the study analyzes secondary data from primary, secondary, and tertiary legal sources. The findings reveal that Indonesia's low tax ratio and widespread taxpayer non-compliance, including forgery, underreporting, and asset concealment, remain significant challenges for tax policy. These challenges stem from both suboptimal tax collection mechanisms and taxpayer resistance. Despite the controversy surrounding tax amnesty, the law plays a strategic role in providing legal certainty, encouraging honest reporting, and increasing state revenue, which is essential for national development.